Macrophages, dendritic cells, and regression of atherosclerosis - Feig, Jonathan E.; Feig, Jessica L. (Frontiers in Physiology, 2012)
Atherosclerosis is the number one cause of death in the Western world. It results from the interaction between modified lipoproteins and monocyte-derived cells such as macrophages, dendritic cells, T cells, and other cellular elements of the arterial wall. This inflammatory process can ultimately lead to the development of complex lesions, or plaques, that protrude into the arterial lumen. Ultimately, plaque rupture and thrombosis can occur leading to the clinical complications of myocardial infarction or stroke. Although each of the cell types plays roles in the pathogenesis of atherosclerosis, in this review, the focus will be primarily on the monocyte derived cells- macrophages and dendritic cells. The roles of these cell types in atherogenesis will be highlighted. Finally, the mechanisms of atherosclerosis regression as it relates to these cells will be discussed.